The Influence Of Lifestyle, Trust, And Perceived Ease Of Use On Decisions To Use Cash On Delevery (COD) On The Tiktok Shop Application (Study On Students Management Faculty Of Economics And Business Unived) - Aldianto, Ferdy; Soleh, Ahmad; Gayatri , Ida Ayu Made Ermeytha (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Efforts to increase consumer decisions in choosing payment methods can be achieved by understanding various influencing factors such as lifestyle, trust, and perceived ease of use. This study aims to examine the influence of lifestyle, trust, and perceived ease of use on the decision to use the Cash On Delivery (COD) payment method on the TikTok Shop application, specifically among Management students of the Faculty of Economics and Business at Dehasen University Bengkulu. The sample in this study consisted of active students in the Management study program at Dehasen University Bengkulu. Data were collected through questionnaires and analyzed using multiple linear regression, validity and reliability tests, as well as hypothesis testing both partially and simultaneously. The regression analysis results show that lifestyle (X₁), trust (X₂), and perceived ease of use (X₃) simultaneously have a significant effect on the decision to use COD (Y). Partially, trust and perceived ease of use have a positive and significant effect on the decision to use COD, while lifestyle does not show a significant influence. The coefficient of determination (R²) of 0.585 indicates that 58.5% of the variance in the decision to use COD can be explained by the three independent variables, while the remaining 41.5% is explained by other factors outside this study. These findings suggest that trust and perceived ease of use are critical factors in encouraging consumers to choose COD as a payment method in the TikTok Shop e-commerce platform.